THE RISE AND FALL OF EXPORT-LED GROWTH - Palley, Thomas I. (Investigación Económica, 2013)
This paper traces the rise of export-led growth as a development paradigm and argues it is exhausted owing to changed conditions in emerging market (EM) and developed economies. The global economy needs a recalibration that facilitates a new paradigm of domestic demand-led growth. Globalization has so diversified global economic activity that no country or region can act as the lone locomotive of global growth. Political reasoning suggests EM countries are unlikely to abandon export-led growth, and nor will the international community implement the international arrangements needed for successful domestic demand-led growth. Consequently, the global economy likely confronts asymmetric stagnation.